Aplicações do setor John da Gravidade de Horndeski nos cenários de brana negra e relações de viscosidade/entropia, mundo brana e cosmologia - Santos, Fabiano Francisco dos (2020)
In this thesis, we approached the applications of the John sector of the Horndeski gravity in the scenarios of black brane, braneworld and cosmology. Specially, we study AdS/CFT correspondence in the context of the Horndeski gravity to evaluate the viscosity/ entropy density ratio, as a function of the fixed exponent and parameters of theory. In the braneworld, we address the issue of nding braneworld solutions in a ve-dimensional Horndeski gravity and discuss gravity localization. Finally, in the cosmological scenario we nding solutions by using rst-order formalism in the Horndeski gravity that constrains the superpotential and implies that no free choice of scalar potential is allowed. The scalar field equation of state reflects well the cosmological scenario at the present time and allows us to conclude that it can simulate the dark energy in the Horndeski gravity.